"Galeria Libertaria". With allegory of the destruction of the bourgeois society. "Apendice del Almanache la Questione Sociale para 1900" (1899)
"Galeria Libertaria". With allegory of the destruction of the bourgeois society. "Apendice del Almanache la Questione Sociale para 1900".